Selection of Export Destination Countries for Home Industry Products Using Multiple Linear Regression Dummy Many Criteria - I Putu Artaya; I Gede Arimbawa; Achmad Muchayan (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: The purpose of this research is to assist home industry products that are eligible for export in choosing the export destination country with the highest economic value. There are three export destinations, i.e Europe, the Middle East and Southeast Asia. Design/methodology/approach: Based on a sample of business actors in eight cities, several primary data were obtained which became the main data for analysis, through a certain approach, namely the analysis and estimation process, the results obtained that the analysis used in this study could be used as an approach to determine the answer to the problem, i.e Regression Multiple Linear Dummy Many criteria that can be used to determine the choice of export destination countries. Findings: There are no other studies that use dummy multiple linear regression analysis with many criteria in the estimation process in finding answers to existing cases. This analysis process turns out to be easier and more accurate when used in the estimation process. So that it becomes a separate alternative in the research analysis method. Therefore, this research can be a solution to the difficulty level of estimation that has been done by other researchers. Paper type: Research paper